Constitutionalism of Cadiz and Independence in Central America: a Tight Historiographical Balance - Herrera Mena, Sajid Alfredo (2021)
In this article we propose to carry out a brief analysis of how the relationship between Cadiz's Constitutionalism, Independence and the beginnings of Republican life in Central America has been understood. To do this, we make a historiographic journey of a little more than 50 years, starting from the studies of Jorge Mario García Laguardia and Mario Rodríguez, to then discuss the interpretive changes that have arisen since the 1990s within three thematic areas: Representation, Local powers and Political Culture. We have focused on political, cultural and intellectual history because that is where the work on the matter has been concentrated.